Spectroscopic and Molecular Docking Investigations on the Effect of the Interaction Between Cefoperazone Sodium and Papain to Drug Efficacy. Issue 2 (4th March 2019) - Zhang, H.C.; Liu, B.S.; Cheng, X.; Wang, C.D.
Abstract: Under the experimental condition of pH=7.40, papain (PAPA) was used as the detection object, and the binding behavior of cefoperazone sodium (CFZ) and PAPA at three temperatures was studied by multi-spectroscopy and molecular docking. The results showed that CFZ can effectively quench the endogenous fluorescence of PAPA, form a 1:1 complex, and change the conformation of PAPA. At 293 K, the fluorescence intensity of the system had a good linear relationship with the CFZ concentration in the range of 4.0×10 -6 ∼ 1.0×10 -4 mol/L. The detection limit of the method was 2.43×10 -6 mol/L (n=10), indicating that the reaction can be used to achieve rapid determination of CFZ content in the actual drug. Based on the experimental data, a mathematical model combining CFZ and PAPA was established. When the peak plasma concentration of CFZ was 106.0 mg/L after intravenous infusion of 1 g, the drug binding rate of CFZ-PAPA system was 2.70 %, indicating the combination of CFZ and PAPA did not affect the efficacy of CFZ, that is, when taking CFZ, it is safe to consume PAPA. Molecular simulation studies had showed that the interaction between CFZ and PAPA had not only electrostatic forces but also hydrogen bonding, which was consistent with the results of spectroscopy and thermodynamic studies.